Height dependent molecular trapping in stacked cyclic porphyrin nanorings - Wieland, Maria B.; Perdigão, Luis M.A.; Kondratuk, Dmitry V.; O'Shea, James N.; Anderson, Harry L.; Beton, Peter H. (Royal Society of Chemistry, 2014)
Stacked layers of cyclic porphyrin nanorings constitute nanoscale receptacles with variable height and diameter which preferentially adsorb sublimed molecules. Using scanning tunnelling microscopy we determine the filling capacity of these nanoring traps, and the dependence of adsorbate capture on stack height and diameter.